Associação entre dor, sedoanalgesia e mortalidade em terapia intensiva - Silva, Daniele Cristiny da (2017)
Intensive Care Unit can generate a highly stressful environment where patients experience experiences of physical and psychological discomfort such as pain, which when untreated can contribute to an unfavorable outcome and increased mortality. The identification of pain through validated scales is indispensable for its proper management. The use of sedatives and analgesics in critical patients is necessary, providing analgesia, anxiolysis, amnesia, and comfort, but these drugs are not free of side effects and require vigilance. Objectives: To associate pain, sedoanalgesia and mortality; Describe the clinical profile, self-report and behavioral pain intensities and sedation levels; To verify the efficiency of the Sequential Organ Failure Assessment as a prognostic index and to identify the validity of pain and its intensities as predictive of mortality. Methods: A cross-sectional and prospective study in a general / neurological clinical / surgical intensive care unit of a tertiary-level hospital, with a sample of 240 patients. Results: Prevalence of non-elderly, male, neurological, surgical patients with deep sedation. There was higher mortality in patients with deep sedation, intense pain, surgical and elderly, and longer hospitalization time in those with moderate sedation. The sedoanalgesia did not suppress the pain, but it controlled its intensity, being Fentanil the drug more used. The Sequential Organ Failure Assessment did not act as a good prognostic index, since the intense pain proved to be a good predictor of mortality. Conclusion: It is concluded that the identification of pain intensities and sedation performed by nurses through validated scales, assists in decision making and bases the appropriate management of sedoanalgesia in intensive care.